The Effects of Different Training Interventions on Soccer Players’ Sprints and Changes of Direction: A Network Meta-Analysis of Randomized Controlled Trials - Kuan Dong; Guyeol Jeong; Buongo Chun (Applied Sciences, 2022)
Objective: To compare and rank the effects of different training interventions on the sprint and change of direction (COD) abilities of soccer players using a network meta-analysis. Methods: The PubMed, Cochrane, and Web of Science databases were searched for papers published up to June 2022. Inclusion criteria: (1) No distinction was made between nationality, region, or gender. No distinction was made between physical activity times or habits. Healthy and disease-free soccer players (age ≥ 18 years old) were eligible. (2) Different training methods and their combinations were used. (3) Groups of either no training or single training, or combined training were included. (4) Randomized controlled trials (RCTs) were included. (5) The outcome indicators included at least one of the following: sprint, agility, and change of direction (COD). Exclusion criteria: (1) studies in non-English were not included. (2) Individual studies, general public studies, literature review studies, qualitative studies, case studies, and studies with unclear data such as means and standard deviations were not included. (3) Studies using the same data were not included. (4) Interventions that could not be statistically analyzed because of insufficient numbers of studies were not included. RCTs that satisfied the inclusion criteria were included. Paired analyses and network meta-analyses were performed using random-effects models. The included studies were assessed using the Cochrane risk-of-bias assessment tool. The surface under the cumulative ranking curve (SUCRA) metric was used to rank the effectiveness of each treatment and identify the best treatment. Results: The network meta-analysis (NMA) included eleven RCTs with a total of two-hundred and seventy-seven participants and six interventions: plyometrics combined with sprint, agility, and resistance training (P+T+S+A), plyometrics combined with sprint and agility training (P+S+A), resisted sprinting combined with agility training (RS+A), plyometric training (P), resistance training (T), soccer skills, and a strategy training control group (C). P+T+S+A ranked highest in terms of improving soccer players’ 10 m sprint performance (SUCRA = 70.2%) and COD (SUCRA = 75.0%). P+S+A ranked highest in terms of improving soccer players’ 20 m sprint performance (SUCRA = 69.8%). Conclusions: Based on the network meta-analysis, for combined training, P+T+S+A was more effective at improving the sprinting and COD ability of soccer players. In the single training mode, plyometric training was the most effective. To improve sprint and COD ability, P+T+S+A should be chosen. Such improvements may be expected after P+T+S+A interventions for a duration of six or more weeks. However, gender, competitive level, and other factors will affect the assessment results. Given the limitations of the above analysis, these results should be interpreted with caution.